Dampak fenomena penutupan Tik Tok shop terhadap perubahan prilaku konsumen studi kasus mahasiswa Institut Ilmu Keislaman Annuqayah (INSTIKA) Guluk-guluk Sumenep - Isyadatul Hasanah; Anna Zakiyah Hastriana (Riviera Publishing, 2024)
The closure of TikTok shop is a policy that has changed the pace of online business, having a significant impact on consumers. This policy has received widespread attention from various groups, including INSTIKA students who are active consumers on TikTok shop. This study aims to analyze how the closure of TikTokshop impacts consumer behavior and online purchase preferences. This study aims to analyze how the closure of TikTokshop impacts consumer behavior and online purchase preferences. This research uses a qualitative approach, with descriptive analysis, looking for information based on existing data, analyzing and interpreting it. Observations and interviews, with 20 informants were used as material in the collection of research data. The results of this study show that the closure of TikTokshop forces consumers, including INSTIKA students, to look for alternatives to meet their shopping needs. Observations and interviews, with 20 informants were used as material in the collection of research data. The results of this study show that the closure of TikTok shop forces consumers, including INSTIKA students, to look for alternatives to meet their shopping needs. Previously, they actively shopped through TikTok shop, but with the closure of this platform, they had to adapt to different online shopping methods. In addition, the closure of TikTok shop also affected the purchasing preferences of College Students, who previously tended to follow trends that were popular on TikTok in terms of fashion, accessories, and other products. However, after closing, they will turn to other sources in making purchasing decisions.